Técnicas activas en el aprendizaje de los Estudios Sociales del octavo "A" de la Escuela de Educación Básica “Miguel Riofrío”, Loja 2021-2022. - Merino Lozano, Nayely Michelle (2022)
The current study is focused on promoting and sustaining the benefits of active techniques during the learning of the subject of Social Studies, so that teachers establish educational scenarios that motivate, stimulate and reinforce the student's knowledge. The general objective is to contribute to the improvement of the learning process through the use of active techniques in the subject of Social Studies, in the eighth parallel year "A" students, evening section of the School of Basic Education "Miguel Riofrío". Likewise, for the development of the methodology of the research work, the mixed approach was used because the strengths of the qualitative and quantitative methodology were taken, the first allowed us to examine the data numerically and the second gave the possibility of describing the qualities of the object of study, also during the process the methods of study were applied as deductive/inductive, analytical, synthetic, statistical, and hermeneutic. Likewise, for the collection of information, techniques such as observation and survey were used, which made it possible to identify deficiencies or strengths of the selected sample. Finally, to conclude, it should be mentioned that, among the most significant results of the active techniques applied by the teacher during the learning process in the students of the Social Studies course, are collaborative learning, graphic organizers and expositions. Key words: Active techniques, learning, social studies, difficulties, skills.